MAIN DIRECTIONS OF IMPROVEMENT OF THE PROCESS OF INVESTMENT ATTRACTION - Baxriddin Jurayevich, Mahmudov; Mukhtasar Fazliddin qizi, Abdurakhmanova (International Journal of Business, Law, and Education, 2020)
In this fast-changing world, conflicts of interest and rivalry between countries are growing. In such a difficult international environment, it is important to keep our country competitive in the region and in the world. Based on the “Strategy of actions on social and economic development of the Republic of Uzbekistan for 2017-2021” adopted for achievement of this goal, the priority directions of our development for the next years are clearly defined. In particular, 76 thousand projects totaling $ 21 trillion and $ 1 billion have been implemented within the framework of the state program "2018 to support active entrepreneurship, innovative ideas and technologies". Significant results are being achieved in the national economy in industry, agriculture, capital construction, transport and communications, services and services. Studies show that total investment in fixed assets at the expense of all sources of economic and social development of the Republic of Uzbekistan amounted to 68.4 trillion soums (US $ 13.4 billion) in 2017, an increase of 120.4% compared to 2016. The share of investment in fixed assets in GDP was 26.9%, compared with 2016 at 2.8% (18.8% compared to 1991, 22.9% against 2000, 19.9% against 2005). It increased by 24.6% compared to 2010 and by 24.3% compared to 2015.